Estimation of repeatability and genetic selection of aromatic cacao trees with genetic material from EE-INIA-San Martin and UC Lebuaf in Peru - Oliva, Carlos (2014)
Cocoa farming is one of the most important activities in the Peruvian Amazon. Its genetic basis is supported by the introduction of improved clones, so that the local genetic potential are in germplasm bank is not well used due to limited breeding study. This study aimed to estimate the repeatability for the genetic selection of high-yield trees with aromatic cocoa beans. Genetic selection analysis was executed with the SOFTWARE SELEGEN REML / BLUP in a 3-year data for assessing grain yield kg / tree, average grain weight (g) and average weight of cobs (kg) in the bank germplasm INIA-San Martin and Lebuaf Conservation Unit SAC (Plantation Maria). The individual repeatability grain yield / tree and average grain weight was moderate (0.52) and (0.30) respectively, which did not happen for the repeatability of the variable average cob weight was low with (0.24). The variable was more stable grain yield / tree, who threw an average of 3 harvest repeatability was 0.77, favoring selective accuracy of 0.88. Superior genotypes can be accurately selected with 4 to 5 harvests. The selection and cloning of the 20 best genotypes or selected trees should facilitate a genetic gain of 112%, raising the annual average productivity of 1.24 grains per tree kg / tree to 1.54 kg / tree.